Impact of Hemodialysis on Visual Parameters in Patients With End-stage Renal Disease (Iranian Journal of Kidney Diseases, 2012)
Introduction. Patients with end-stage renal disease who receive hemodialysis are prone to visual disturbances. The aim of this study was to evaluate the effects of metabolic changes on visual parameters during hemodialysis sessions.  Materials and Methods. Demographic information including history of underlying diseases, wearing eyeglasses, any ocular diseases or surgeries, and hemodialysis duration and frequency were recorded in 65 hemodialysis patients. The best corrected visual acuity (BCVA) in logarithm of the minimum angle of resolution and spherical equivalent (SE) per diopter were measured before and after hemodialysis. Other systemic and metabolic parameters including systolic blood pressure, body weight, KT/V, and blood levels of glucose, urea, and sodium were recorded. Results. A total of 130 eyes of 38 men and 27 women with ages ranged from 24 to 90 years (mean, 60.3 ± 16.7 years) were enrolled. The mean BCVA changed significantly after hemodialysis (0.29 ± 0.48 increased to 0.31 ± 0.49; P < .001). The mean SE changes were significant as well (-0.33 ± 0.31 D decreased to -0.40 ± 0.12 D; P < .001). There was a weakly positive correlation between the BCVA and blood glucose changes (P = .05, r = 0.166). There were significant associations between diabetic retinopathy and wearing of eyeglasses with BCVA and SE (P < .001 for both).   Conclusions. Hemodialysis could influence on visual parameters such as BCVA and refractive status by means of changes in blood glucose or possibly other systemic parameters.